3D Multiscale-Multiphysics SOFC Modelling Status at the Institute of Electrochemical Process Engineering, FZ Jülich. (2nd June 2015) - Peksen, Murat; Al-Masri, Ali; Peters, Roland; Blum, Ludger; Stolten, Detlef
Abstract : The Institute of Electrochemical Process Engineering (IEK-3), SOFC modelling research group has been giving particular attention to the 3D multiscale-multiphysics modelling of SOFC systems during the last seven years. Focus has been the coupled thermochemical fluid flow and thermomechanical interactions of SOFCs, auxiliary components, as well as complete fuel cell systems. Currently, emphasis of research has been given to the material, process and 3D design optimisation of APU fuel cell stacks, micro modelling of cells and the full scale high-end 3D system level multiphysics modelling and optimisation. Therby, an important investigation field has been the various geometrical component scales, including macro, meso, and micro level by coupling the experimentally validated numerical predictions from system level down to the component and cell level. Coupled CFD/FEM is used to predict the thermochemical fluid flow, heat radiation, electrochemical and species transport, creep deformation, elastoplasticity and cyclic behaviour.